Utilization of solid wastes in construction materials - Safiuddin, Md.; Jumaat, Mohd Zamin; Salam, M.A.; Islam, M.S.; Hashim, Roslan (Academic Journals, 2010)
The main objective of this study is to investigate the potential use of various solid wastes for producing construction materials. The paper is based on the comprehensive review of available literature on the construction materials including different kinds of solid wastes. The traditional methods for producing construction materials are using the valuable natural resources. Besides, the industrial and urban management systems are generating solid wastes, and most often dumping them in open fields. These activities pose serious detrimental effects on the environment. To safeguard the environment, many efforts are being made for the recycling of different types of solid wastes with a view to utilizing them in the production of various construction materials. This paper discusses the environmental implications caused by the generation of various solid wastes, and highlights their recycling potentials and possible use for producing construction materials. In addition, this paper shows the applications of solid waste based construction materials in real construction, and identifies the research needs.